Plurihormonal Pituitary Neuroendocrine Tumors: Clinical Relevance of Immunohistochemical Analysis - Dumitriu-Stan, Roxana-Ioana; Burcea, Iulia-Florentina; Dobre, Ramona; Nastase, Valeria Nicoleta; Ceausu, Raluca Amalia; Raica, Marius; Poiana, Catalina (Diagnostics (Basel), 2024)
Plurihormonal pituitary neuroendocrine tumors (PitNETs) are rare forms of tumors that express more than one hormone. The most common association is between growth hormone (GH) and prolactin (PRL), but other unusual combinations have been reported, such as GH and ACTH. Usually, the clinical dominance in these cases is related to GH hypersecretion. In these cases, immunohistochemistry (IHC) of transcription factors (TFs) is very useful for an accurate diagnosis. We included 42 patients diagnosed with pituitary neuroendocrine tumors (PitNETs): 37 patients with a confirmed diagnosis of acromegaly, and 5 patients with prolactinomas. All patients underwent transsphenoidal surgical intervention. We correlated the immunohistochemical features of plurihormonal PitNETs with clinical, hormonal, and imaging data. Tumor specimens were histologically and immunohistochemically examined. Based on the 2022 WHO classification, using IHC, 13 patients exhibited positive staining for more than one hormone, while unusual combinations like GH + ACTH and PRL + ACTH were also identified in other cases. Unusual cell combinations that produce hormones unrelated histogenetically, biochemically, or through regulatory mechanisms can appear and may display aggressive behavior, persistent disease, and high recurrence. We have not identified a clear correlation with the prognosis of these rare PitNETs.